Enhanced reusability of horseradish peroxidase immobilized onto graphene oxide/magnetic chitosan beads for cost effective cholesterol oxidase assay - Sahu, Shraddha; Shera, Shailendra Singh; Banik, Rathindra Mohan (Bentham Science Publishers, 2019)
Background: Horseradish Peroxidase (HRP) is an important biocatalyst extensively used in enzymatic reactions. Cholesterol oxidase (ChoX) is a commercially valuable enzyme used in the estimation of cholesterol in human serum. ChoX is an oxygen oxidoreductase class of enzyme which catalyzes the oxidation of cholesterol in the presence of O2, liberating hydrogen peroxide H2O2 as a by-product. HRP catalyzes the reduction of this H2O2 in the presence of a redox dye (chromophore), producing a pink colored Quinoneimine which can be measured spectrophotometrically. The use of soluble HRP makes this assay method expensive for each time use and the recovery of HRP is not possible. Objective: Our aim was to prepare the HRP immobilized beads having magnetic properties for the ease of separation and increasing the reusability of HRP for the low cost ChoX assay. Methods: In the present work, we prepared magnetic chitosan beads using chitosan-Fe2O3 nanoparticle blend coated with Graphene Oxide (GO), and subsequently activated with 2.5% glutaraldehyde (GA). Enzyme loaded beads were characterized by SEM, FTIR, and XRD analysis. Results: The immobilization efficiency was ~80% and the immobilized HRP retained 90% of its initial activity up to 12 times reuse. The pH and temperature optima were shifted from 6.5 and 50°C for soluble HRP to 7.0 and 55°C for the immobilized HRP, respectively. Storage stability of immobilized HRP was 93.72% and 60.97% after 30 and 60 days storage respectively, at 4°C. Conclusion: On the basis of the present study, the HRP loaded magnetic chitosan/graphene oxide beads could be used for low-cost ChoX assay at laboratory scale due to its enhanced reusability and stability.
Keywords: Chitosan; Cholesterol oxidase; Graphene oxide; Horseradish peroxidase; Immobilization; Magnetic nanoparticles; Reusability